The Decisive Factors in Selection of Architects according to the Developers of Apartment Projects in Surabaya - Melita Darmanto; Herry Pintardi Chandra; Paul Nugraha (Petra Christian University, 2019)
Selection of an architect is not as easy as buying finished goods becausetheir services are intangible. The selection of architect consists of several variables,namely task performance, contextual performance, network relationships andprices. The purpose of this study is to analyze which factors are most decisive inselecting an architect according to apartment developers in Surabaya, and toanalyze whether there are differences between the factors in each variable. Thisstudy used a pilot study with a questionnaire method that was distributed to thearchitect lecturers of Petra Christian University, Indonesia. The results of the pilotstudy were re-synthesize and distributed to apartment developers in Surabaya. Theconclusion is that the most decisive factor in task performance variable is a creative,innovative, and constructability.